Penerapan Asas Kepentingan Militer terhadap Prajurit TNI yang Melakukan Tindak Pidana dalam Sistem Peradilan Militer di Indonesia - Wicaksono, Aditya; Sagala, Parluhutan; Jaeni, Ahmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This article examines the application of the military necessity principle in the Indonesian Military Justice system, with a focus on the case of Military Court Decision Number 8-K/PM.III-19/AD/I/2023 in Jayapura. This study examines how military courts interpret the principle of military necessity and balance it with the concept of justice and criminal theory. The decision in this case, which took into account the military court judge's decision to maintain territorial security, decided lighter than what was demanded by the Military Prosecutor. This study examines the application of the principle of military necessity by considering the theory of punishment and dignified justice.